2022
DOI: 10.1109/access.2022.3171984
|View full text |Cite
|
Sign up to set email alerts
|

BEAT: Blockchain-Enabled Accountable and Transparent Infrastructure Sharing in 6G and Beyond

Abstract: It is widely expected that future networks of 6G and beyond will substantially improve on 5G. Technologies such as Internet of Skills and Industry 4.0 will become stable and viable, as a direct consequence of networks that offer sustained and reliable mobile performance levels. The primary challenges for future technologies are not just low-latency and high-bandwidth. The more critical problem Mobile Service Providers (MSPs) will face will be in balancing the inflated demands of network connections and custome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Distributed ledger technology has emerged as an enabler for accountability and transparency in cloud computing [124] and network service [125]. Expanding on the application of blockchain technology, Singh et al [126] delved into its potential to enhance the transparency and security of electronic health records.…”
Section: Blockchain-enabled Platforms For Data Exchange and Service P...mentioning
confidence: 99%
“…Distributed ledger technology has emerged as an enabler for accountability and transparency in cloud computing [124] and network service [125]. Expanding on the application of blockchain technology, Singh et al [126] delved into its potential to enhance the transparency and security of electronic health records.…”
Section: Blockchain-enabled Platforms For Data Exchange and Service P...mentioning
confidence: 99%
“…The authors in [16] Uses distributed ledger technology's permission-type properties to ensure accountability and transparency while sharing infrastructure among providers. Testing on a low-resource device shows that BEAT adds only a few seconds to processing.…”
Section: Related Workmentioning
confidence: 99%
“…Simulation demonstrates that this combination can store the public keys of IoT devices on the blockchain and efficiently route network traffic using SDN. Similarly, Siddiqui et al [122] observed that with the assistance Distributed ledger technology has emerged as an enabler of accountability and transparency in cloud computing [123] and network service [124]. Expanding on the application of blockchain technology, Singh et al [125] delved into its potential to improve the transparency and security of electronic health records.…”
Section: Blockchain-enabled Platforms For Data Exchange and Service P...mentioning
confidence: 99%